Model za razvrščanje izdelkov kosovnega pohištva iz lesa glede na obremenjevanje okolja med procesom izdelave - Lipušček, Igor (Zbornik gozdarstva in lesarstva, 2003)
There are many parameters influencing environmental burdening in the process of wooden furniture production. The aim of this research was to ascertain the key parameters and to form a model for classifying these products regarding their environmental burdening. The multi-criteria decision-making method was used for the model formation. Utility functions were calculated with the analytic hierarchy processes method (AHP) on the basis of prior statistically processed expert finding. The mathematical model formation enables a critical comparison of products from the viewpoint of environment threatening as well as exposure of explicit advantages and disadvantages of a certain product.
Keywords: lesna industrija; odločitveni modeli; onesnaževanje okolja; razvrščanje; večkriterijsko odločanje